High-frequency robust position control of a nonlinear piezoelectric bending actuator. (16th January 2020) - Shahabi, Pouyan; Ghafarirad, Hamed; Taghvaeipour, Afshin
Piezoelectric bending actuators have been widely used in a variety of micro- and nano-applications, including atomic force microscopy, micro assembly, cell manipulation, and in general, micro electromechanical systems. However, their control algorithms at low frequencies suffer from nonlinearities such as hysteresis in high voltages and creep in long-time static applications. Also, in high-frequency applications, especially near the actuator natural frequencies, the actuator dynamic is greatly affected by the material nonlinearity. Therefore, the control approaches based on the linear dynamic modeling cannot be effective at high frequencies. Thus, the position control of the foregoing actuators become challenging, and it has been of researchers' interests in the last decade. In this article, the robust position control of a bimorph piezoelectric bending actuators is investigated. In this regard, based on the nonlinear constitutive equations and the Euler–Bernoulli beam theory, a nonlinear dynamic model is presented. Then, to track a desired motion trajectory, an observer-based robust position control algorithm is proposed. The proposed control methodology is able to accommodate parametric uncertainties and other un-modeled dynamics. Also, it ensures the elimination of the position tracking error in the presence of the estimated states. Finally, the tracking ability of the controller is demonstrated in an experimental study. The experimental results show that the identification of the system is properly conducted with the average error of 5.5%. Also, the efficiency of the robust controller is proved with the error of 3.7% and 4.9% in the position tracking of the actuator inside and outside of the identified region, respectively.